The Role of Artificial Intelligence and Smart Media in the Development of Tourism Services - Ulugmurodov Farkhod Faxriddinovich; Qarshiyev Avazbek Sa’dullayevich; Akbarov Javohir Vohid o‘g‘li (Scientific Trends, 2023)
This article explores the role of artificial intelligence and smart media devices in the development of tourism services. The analysis focuses on the impact of artificial intelligence and smart media devices on enhancing the tourism experience, offering personalized services to clients, organizing travel and accommodations, providing tourism-related information, and incorporating the growth of technological innovations in the tourism industry.
Keywords: Artificial intelligence, mobile technology, smart media, preferences, automation, smart media.